2010
DOI: 10.1002/pola.23915
|View full text |Cite
|
Sign up to set email alerts
|

A novel type of optically active helical polymers: Synthesis and characterization of poly(α,β‐unsaturated ketone)

Abstract: New a,b-unsaturated ketone monomers, menthyl vinyl ketone (MVK), and 1-menthylbut-3-en-2-one (MBEK) were synthesized. The monomers were polymerized using butyllithium as an initiator. The polymer derived from MVK (poly-MVK) had a tremendous specific optical rotation [a] 25 365 , which was as 32 times large as that of its monomer MVK. Poly-MVK was confirmed to keep a prevailing helicity of backbone in solution by means of comparing the specific optical rotation and the CD spectra with that of MVK and the model … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 44 publications
(47 reference statements)
0
11
0
Order By: Relevance
“…MVK, [α] 36525 = +26.9° ( c = 0.010, toluene), was prepared by means of the method described by ref 41…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…MVK, [α] 36525 = +26.9° ( c = 0.010, toluene), was prepared by means of the method described by ref 41…”
Section: Methodsmentioning
confidence: 99%
“…However, in poly(triphenylmethyl methacrylate), the bulky triphenylmethyl, which is responsible for chirally helical sense, suffers solvolysis by methanol, which is often used as a suitable eluent for HPLC. More recently, our group has successfully prepared optically active helical poly(menthyl vinyl ketone) (poly‐MVK) by anionic polymerization of MVK 41. The poly‐MVK overcomes thoroughly the disadvantage of the methanolysis because there is no ester linkage between the bulky group and the main chain backbone.…”
Section: Introductionmentioning
confidence: 99%
“…So far, a large amount of polymers that keep a single-handed helical conformation in solution have been prepared from methyl methacrylate [1,4], styrenes [5][6][7][8][9][10][11], aldehydes [12,13], acrylamides [14][15][16][17][18], acetylenes [19][20][21][22] and so on. However, to our knowledge, there was little information about the single-handed helical polymer derived from a, b-unsaturated ketone [23,24]. Optically active polymers with a stable one-handed helicity may be important for enhancing their chiral recognition or discrimination ability toward enantiomers.…”
Section: Introductionmentioning
confidence: 94%
“…Asymmetrical a,b-unsaturated ketone derivatives became research targets of great significance because they could perform chiral recognition and organocatalysis functions. On the other hand, investigations from us showed that substituted a,bunsaturated ketone could form stable helical conformation via polymerization under suitable conditions [7][8][9][10]. As we know, preferred-handed helical poly(triphenylmethyl methacrylate) [poly(TrMA)] exhibits a high chiral recognition as a chiral stationary phase in high-performance liquid chromatography (HPLC) to resolve a wide range of racemates [11][12][13].…”
mentioning
confidence: 98%